Discovering Poverty and Its Influencing Factors in the Capital City of Nusantara (IKN) - Dio Caisar Darma; Priyagus Priyagus; Rosyadi Rosyadi; Arfiah Busari; Angga Yogaswara (Jurnal Ekonomi Pembangunan, 2026)
This paper explores the causality between per capita expenditure (PCE), unemployment (Umt), and labour supply (LS) on poverty (Pvt) through health quality (HQ) in the IKN region during 2016–2024. The rationale for this research is that the IKN project has the potential to rapidly transform the labour market and economic structure, meaning that the impact of economic growth on poverty is influenced not only by the scale of economic activity itself but also by the population’s health capacity to respond to economic pressures and opportunities. Furthermore, health quality plays a crucial role in enhancing or diminishing the effectiveness of expenditure and employment opportunities in reducing poverty; therefore, neglecting this element risks producing IKN development policies that are neither inclusive nor sustainable. The Ordinary Least Squares (OLS) method was employed to analyse secondary panel data, which was adapted into a multiple regression and moderation model, yielding three key findings. First, PCE and Umt have a significant effect on HQ. Second, Umt, LS, and HQ significantly influence Pvt. Third, PCE and Umt, moderated by HQ, are shown to have a significant effect on Pvt. Among the variables examined, only Umt consistently plays a significant role in extending HQ or reducing Pvt.